Olaparib maintenance monotherapy in Chinese patients with platinum‐sensitive relapsed ovarian cancer: China cohort from the phase III SOLO2 trial. Issue 6 (31st March 2022) - Liu, Jihong; Yin, Rutie; Wu, Lingying; Zhu, Jianqing; Lou, Ge; Wu, Xiaohua; Zhou, Qi; Gao, Yunong; Kong, Beihua; Lu, Xin; Wang, Jing; Chen, Youguo; et al.
Abstract: Aim: The phase III SOLO2 global study demonstrated the efficacy and safety of maintenance olaparib, a poly(adenosine diphosphate‐ribose) polymerase inhibitor, in platinum‐sensitive relapsed ovarian cancer patients with a BRCA mutation. This separate China cohort of SOLO2 investigated the efficacy and safety of maintenance olaparib in Chinese patients. Methods: Patients received olaparib (300 mg twice daily, oral, tablets) or matched placebo. Primary endpoint was investigator‐assessed progression‐free survival (Response Evaluation Criteria in Solid Tumors version 1.1). Safety and tolerability were also assessed. Results: Thirty‐two patients were treated. Olaparib treatment led to an improvement in progression‐free survival compared with placebo (hazard ratio = 0.44, 95% confidence interval: 0.17–1.19; median = 13.8 vs. 5.5 months). Results of secondary efficacy endpoints of time to first subsequent treatment/death and time to treatment discontinuation/death were consistent with progression‐free survival results. Time to second progression/death and time to second subsequent treatment/death data were immature at data cutoff. The most common adverse events in the olaparib arm were nausea (81.8%), anemia (45.5%), and decreased appetite (36.4%). Grade ≥3 adverse events were experienced by 36.4% of olaparib and 10.0% of placebo patients. No adverse events led to discontinuation of treatment. There were six deaths (olaparib, five; placebo, one); one death in the olaparib arm was due to an unknown cause, all others were related to disease progression. Conclusions: Efficacy and safety findings in the China SOLO2 cohort support the use of olaparib (300 mg twice daily) as maintenance treatment for Chinese patients with platinum‐sensitive relapsed ovarian cancer and a BRCA mutation. Abstract : In a China cohort (n=32) of the Phase III SOLO2 trial, olaparib maintenance monotherapy (300 mg twice daily) showed a progression‐free survival benefit versus placebo. The most common adverse events in the olaparib arm were nausea, anemia and decreased appetite. These findings are consistent with data from the global SOLO2 population and support the use of olaparib as maintenance treatment for Chinese patients with platinum‐sensitive relapsed ovarian cancer and a BRCA mutation.